Personal Characteristics And Creative Performance Of Indonesian Radio Station Operating Managers : The Impact Of Leader-Member Exchange [HD38.2. N968 2007 f rb ]. - Setiadi, Nugroho Juli (2007)
Kadar pertumbuhan industri penyiaran radio yang pesat di Indonesia telah mengujudkan cabaran khusus ke atas kelebihan pembangunan persaingan.